Knowledge, attitude, practice and learning needs of nursing personnel related to domestic violence against women: a facility based cross sectional survey - Sharma, Kamlesh Kumari; Vatsa, Manju; Kalaivani, Mani; Bhardwaj, Daya Nand (International Journal Of Community Medicine And Public Health, 2018)
Background: Domestic violence against women (DVAW) is widely recognized as a public health problem. In India, health sector response to DVAW is suboptimal. Present study aimed to assess the knowledge, attitude, practice and learning needs of nursing personnel regarding women’s health issues related to domestic violence. Methods: This facility based cross sectional study was carried out among 100 nursing personnel from Public sector in Delhi, selected using stratified random sampling. Data were collected using a validated, pretested, structured self reported questionnaire with a few open ended questions. It included knowledge, attitude, practice and learning needs of nursing personnel relevant to DV. Descriptive statistics were used for data analysis using Stata 11.0 (College Station, Texas, USA). Results: Two third of nursing personnel (67%) had moderate knowledge scores and 27% had poor knowledge scores; 19% had favourable attitude scores towards DV; 57% had good practice scores; 44% reported moderate to high need for learning and majority lacked preparedness to manage DV victims. The knowledge was significantly associated with younger age, single, graduate/ Post graduates, B.Sc. Nursing degree holders, working in tertiary hospital, as staff nurse/public health nurse/sister in charge and those with lesser experience, (p<0.05). The attitude was significantly associated with younger age, single, graduate/post graduates, and those with lesser experience, (p<0.05). Conclusions: Nursing personnel had substantial gap in their knowledge, attitude and practice related to DV and a large unmet learning need highlighting the need for relevant pre service and continuing education.